If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 8q = 7 + 7q Solving 5 + 8q = 7 + 7q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-7q' to each side of the equation. 5 + 8q + -7q = 7 + 7q + -7q Combine like terms: 8q + -7q = 1q 5 + 1q = 7 + 7q + -7q Combine like terms: 7q + -7q = 0 5 + 1q = 7 + 0 5 + 1q = 7 Add '-5' to each side of the equation. 5 + -5 + 1q = 7 + -5 Combine like terms: 5 + -5 = 0 0 + 1q = 7 + -5 1q = 7 + -5 Combine like terms: 7 + -5 = 2 1q = 2 Divide each side by '1'. q = 2 Simplifying q = 2
| -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) | | n-12=10 | | 3x+4=6-7x | | 10x^2+1=11X | | -5(n+3)-(7+8n)= | | 2(e-15)=32 | | 3x(-3x+5)=5 | | 37x+20=0 | | x(2-x)(2+x)-x-2= | | 4+x^2=75 | | 5(3X-4)=16x | | 11-(x+8)=3+x | | 11+n=-5 | | 43-7x=2x+18 | | 8y+6=38 | | 11+n= | | -6-4n+3n=20-35 |